Evaluating Indirect Effects of Hunting on Mule Deer Spatial Behavior. Issue 7 (29th June 2020) - Brown, Casey L.; Smith, Joshua B.; Wisdom, Michael J.; Rowland, Mary M.; Spitz, Derek B.; Clark, Darren A.
ABSTRACT: Mule deer ( Odocoileus hemionus ) are widely hunted throughout western North America and are experiencing population declines across much of their range. Consequently, understanding the direct and indirect effects of hunting is important for management of mule deer populations. Managers can influence deer mortality rates through changes in hunting season length or authorized tag numbers. Little is known, however, about how hunting can affect site fidelity patterns and subsequent habitat use and movement patterns of mule deer. Understanding these patterns is especially important for adult females because changes in behavior may influence their ability to acquire resources and ultimately affect their productivity. Between 2008 and 2013, we obtained global positioning system locations for 42 adult female deer at the Starkey Experimental Forest and Range in northeast Oregon, USA, during 5‐day control and treatment periods in which hunters were absent (pre‐hunt), present but not actively hunting (scout and post‐hunt), and actively hunting male mule deer (hunt) on the landscape. We estimated summer home ranges and 5‐day use areas during pre‐hunt and hunt periods and calculated overlap metrics across home ranges and use areas to assess site fidelity within and across years. We used step selection functions to evaluate whether female mule deer responded to human hunters by adjusting fine‐scale habitat selection and movement patterns during the hunting season compared to the pre‐hunt period. Mule deer maintained site fidelity despite disturbance by hunters with 72 ± 4% (SE) within‐year overlap between summer home ranges and hunt use areas and 54 ± 7% inter‐annual overlap among pre‐hunt use areas and 56 ± 7% among hunt use areas. Mule deer diurnal movement rates, when hunters are active on the landscape, were higher during the hunting period versus pre‐hunt or scout periods. In contrast, nocturnal movement rates, when hunters are inactive on the landscape, were similar between hunting and non‐hunting periods. Additionally, during the hunt, female mule deer hourly movements increased in areas with high greenness values, indicating that mule deer spent less time in areas with more vegetative productivity. Female mule deer maintained consistent habitat selection patterns before and during hunts, selecting areas that offered more forest canopy cover and high levels of vegetative productivity. Our results indicate that deer at Starkey are adopting behavioral strategies in response to hunters by increasing their movement rates and selecting habitat in well‐established ranges. Therefore, considering site fidelity behavior in management planning could provide important information about the spatial behavior of animals and potential energetic costs incurred, especially by non‐target animals during hunting season. © 2020 The Wildlife Society. Abstract : Female mule deer are adopting behavioral strategies in response to hunters by increasing their movement rates and selecting habitat in well‐established ranges. We recommend wildlife managers consider multiple temporal and spatial scales when studying anti‐predator strategies of ungulates.